2021
DOI: 10.1016/j.jaad.2020.05.102
|View full text |Cite
|
Sign up to set email alerts
|

One-year real-world clinical effectiveness, safety, and laboratory safety of dupilumab in Japanese adult patients with atopic dermatitis: A single-center retrospective study

Abstract: The sensitivity, specificity, and positive and negative likelihood ratios were 57.7%, 72.3%, 2.08, and 0.59, respectively. (ROC curves were not plotted for case patients aged 2 years or younger because of the small numbers.)There was significant correlation of serum TARC levels with the SCORAD index (r ¼ 0.538; 95% confidence interval [CI], 0.36-0.68), QOL indices (Infants' Dermatitis QOL: r ¼ 0.823; 95% CI, 0.40-0.96; Children's Dermatology Life Quality Index: r ¼ .380; 95% CI, 0.16-0.57), peripheral eosinoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 8 publications
(10 reference statements)
6
34
0
Order By: Relevance
“…While real-world studies on the long-term effectiveness and safety of dupilumab treatment have been conducted and published in various countries 9 14 , there were limited data on its long-term results in Korean AD patients despite our previous study of dupilumab treatment for 16 weeks. In this study, we assessed long-term effectiveness and safety of 52 weeks of continuous treatment with dupilumab in Korean patients with moderate-to-severe AD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While real-world studies on the long-term effectiveness and safety of dupilumab treatment have been conducted and published in various countries 9 14 , there were limited data on its long-term results in Korean AD patients despite our previous study of dupilumab treatment for 16 weeks. In this study, we assessed long-term effectiveness and safety of 52 weeks of continuous treatment with dupilumab in Korean patients with moderate-to-severe AD.…”
Section: Discussionmentioning
confidence: 99%
“…Dupilumab has shown efficacy and safety in existing phase 3 and 4 clinical trials 8 and long-term effectiveness in various real-world studies 9 14 . Previous data from Korea have shown significant improvements and safety in moderate-to-severe AD patients treated with dupilumab for 16 weeks 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Real-world evidence of the effectiveness and safety of dupilumab for atopic dermatitis Accumulating real-world evidence has ensured the effectiveness and tolerable safety of dupilumab both in the short term and in the long term. The articles searched in PubMed and Google Scholar are shown in Table 1 (Ariëns et al, 2020, Ariëns et al, 2021, Faiz et al, 2019, Fargnoli et al, 2020, Fargnoli et al, 2019, Jang et al, 2020, Jo et al, 2020a, Kreeshan et al, 2021, Matsutani et al, 2020, Nettis et al, 2020b, Nettis et al, 2020c, Olesen et al, 2019, Patruno et al, 2021a, Patruno et al, 2021b, Quint et al, 2020, Ribero et al, 2020, Sears et al, 2020, Tauber et al, 2019, Uchida et al, 2021, Uchida et al, 2019. Patruno et al reported the effectiveness and safety of dupilumab in elderly patients with AD in real life (Patruno et al, 2021a, Patruno et al, 2021b.…”
Section: Effectiveness and Safety Of Dupilumab For Atopic Dermatitis In The Real Worldmentioning
confidence: 99%
“…In particular, dupilumab, a fully humanized anti-IL4Rα monoclonal antibody, has demonstrated to have remarkable efficacy and relative safety in the aspects of adverse events in both clinical trials and real-world settings. 2 3 4 5 6 7 8 9 Nonetheless, the cost of dupilumab is quite exorbitant, particularly in Korea, and only a small percentage of patients can be covered by the national health insurance program due to stringent requirements. In spite of the situations where dupilumab can be used, it is often the case that the use of dupilumab is given up for economic reasons.…”
mentioning
confidence: 99%